Who is to suffer? Quantifying the impact of sanctions on German firms - Holger Görg; Anna Jacobs; Saskia Meuchelböck (Kiel Institute for the World Economy (IfW Kiel), 2023)
In this paper, we use a novel firm level dataset for Germany to investigate the effect of sanctions on export behaviour and performance of German firms. More specifically, we study the sanctions imposed by the EU against Russia in 2014 in response to the annexation of Crimea and Russia's countermeasures. We find a substantial negative effect on both the extensive and intensive margin of German exports. While the negative effects are strongest for firms exporting products subject to trade restrictions, we provide further evidence on the indirect effects of sanctions. Analysing the impact on broader measures of firm performance, we document that the cost of sanctions is heterogeneous across firms but overall modest. Our results reveal that the negative impact of the shock was concentrated primarily among a small number of firms that were highly dependent on Russia as an export market and those directly affected by the sanctions.
Keywords: F1; F14; F51; L25; 330; sanctions; foreign policy; trade; firm behaviour; Germany